Intermittent fasting preserves beta-cell mass in obesity-induced diabetes via the autophagy-lysosome pathway. Issue 11 (2nd November 2017) - Liu, Haiyan; Javaheri, Ali; Godar, Rebecca J.; Murphy, John; Ma, Xiucui; Rohatgi, Nidhi; Mahadevan, Jana; Hyrc, Krzysztof; Saftig, Paul; Marshall, Connie; McDaniel, Michael L.; Remedi, Maria S.; et al.
ABSTRACT: Obesity-induced diabetes is characterized by hyperglycemia, insulin resistance, and progressive beta cell failure. In islets of mice with obesity-induced diabetes, we observe increased beta cell death and impaired autophagic flux. We hypothesized that intermittent fasting, a clinically sustainable therapeutic strategy, stimulates autophagic flux to ameliorate obesity-induced diabetes. Our data show that despite continued high-fat intake, intermittent fasting restores autophagic flux in islets and improves glucose tolerance by enhancing glucose-stimulated insulin secretion, beta cell survival, and nuclear expression of NEUROG3, a marker of pancreatic regeneration. In contrast, intermittent fasting does not rescue beta-cell death or induce NEUROG3 expression in obese mice with lysosomal dysfunction secondary to deficiency of the lysosomal membrane protein, LAMP2 or haplo-insufficiency of BECN1/Beclin 1, a protein critical for autophagosome formation. Moreover, intermittent fasting is sufficient to provoke beta cell death in nonobese lamp2 null mice, attesting to a critical role for lysosome function in beta cell homeostasis under fasting conditions. Beta cells in intermittently-fasted LAMP2- or BECN1-deficient mice exhibit markers of autophagic failure with accumulation of damaged mitochondria and upregulation of oxidative stress. Thus, intermittent fasting preserves organelle quality via the autophagy-lysosome pathway to enhance beta cell survival and stimulates markers of regeneration in obesity-induced diabetes.